College Algebra (11th Edition)

Published by Pearson
ISBN 10: 0321671791
ISBN 13: 978-0-32167-179-0

Chapter 4 - Section 4.2 - Exponential Functions - 4.2 Exercises - Page 410: 64



Work Step by Step

We rewrite both sides, so that the base is $\frac{3}{2}$ on both sides. Left side: $\frac{2}{3}^x$. By the law of exponents:$\frac{1}{a}^x=a^{-x}$ $\frac{2}{3}^x=\frac{3}{2}^{-x}$ Right side: $\frac{9}{4}=\frac{3}{2}^2$ Thus, the given equation is equivalent to: $\frac{3}{2}^{-x}=\frac{3}{2}^2$ Since the bases are the same, we set the exponents equal: $-x=2 \\-1(-x)=-1(2) \\x=-2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.